Lymph node FNC : cytopathology of lymph nodes and extranodal lymphoproliferative processes - Zeppa, Pio; Cozzolino, Immacolata (Basel : Karger, 2018)
This well-illustrated monograph presents a comprehensive description of Fine-Needle Cytology (FNC), including technical procedures and ancillary techniques, applied to the lymph node (LN). Possibilities and limitations are highlighted to produce accurate cytological diagnosis of LN and cytological criteria, and to be exploited for extra-nodal lymphoproliferative processes. The normal LN structure and corresponding cytological patterns are described. Cytological, phenotypical, and molecular features are reviewed along with diagnostic criteria for various medical conditions such as lymphadenitis and lymphadenopathies, Hodgkin and Non-Hodgkin lymphoma, pediatric lymphoadenopaties, immunodeficiency-associated lymphoproliferative disorders, extra-nodal lymphoproliferative processes, metastases, and other non-lymphomatous processes. LN-FNC requires knowledge of hemathopathology and imaging techniques, as well as dexterity with FNC performing, smearing, and material management. Rapid on-site evaluation (ROSE), the choice of ancillary techniques and molecular procedures case by case are required to produce accurate and comprehensive diagnosis. This book will help cytopathologists to conduct these tasks in various organs and clinical contexts. LN-FNC requires knowledge of hemathopathology and imaging techniques, as well as dexterity with FNC performing, smearing, and material management. Rapid on-site evaluation (ROSE), the choice of ancillary techniques and molecular procedures case by case are required to produce accurate and comprehensive diagnosis. This book will help cytopathologists to conduct these tasks in various organs and clinical contexts.
Keywords: GANGLIOS LINFÁTICOS -- CITOLOGÍA; TRASTORNOS LINFOPROLIFERATIVOS -- DIAGNÓSTICO; GANGLIOS LINFÁTICOS -- ENFERMEDADES -- PATOLOGÍA; GANGLIOS LINFÁTICOS -- BIOPSIA CON AGUJA; BIOPSIA CON AGUJA FINA; TRASTORNOS LINFOPROLIFERATIVOS